Transforming distance education curricula through distributive leadership - Mike Keppell; Carolyn O`Dwyer; Betsy Lyon; Merilyn Childs (Association for Learning Technology, 2010)
This paper examines a core leadership strategy for transforming learning and teaching in distance education through flexible and blended learning. It focuses on a project centred on distributive leadership that involves collaboration, shared purpose, responsibility and recognition of leadership irrespective of role or position within an organisation. Distributive leadership was a core principle in facilitating the transformation of learning and teaching through a Teaching Fellowship Scheme that empowered leaders across a regional distance education university. In parallel, a design-based research project analysed the perceptions of the Teaching Fellows in relation to blended learning, time/space, peer learning, innovation and equity issues in relation to distance education.